FORMATION OF SOYBEAN GRAIN YIELD DEPENDING ON MEASURES ADAPTIVE TECHNOLOGY UNDER WESTEN FOREST STEPPE - Бахмат, О. М.; Федорук, І. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The results of studies on the formation of soybean grain yield based on measures of adaptive technologies under western forest steppe. Experiments were carried out in LLC "Garant" Kamianets-Podilskyi district of Khmelnitskyi region. The predecessor was soy. After cleaning predecessor flaky stubble conducted to a depth of 22 cm. In three weeks had repeated shelling at a depth of 22 cm. After a month spent on the cultivation of 10-12 cm while leveling soil aggregate Europack. Spring tillage begins with harrowing (mulching). Beforehand spent processing soybean drugs such as insektetsydno - Antifungal Chemical means of physiological effect Standak Top normally 1 l / t and inoculant according to the scheme of the experiment (Hee Drain, Cat Hai). Inoculation of soybean nainnya drug Stick Hui held a day of sowing. Due to lack of moisture held in cultivation planting day (27 April), cultivation was carried out to a depth of 3-5 cm. Sowing conducted April 27, 2016, when the soil temperature at a depth of 10 cm was 12 - 14 0C. When sowing row spacing of 35 cm using drill Svohiya. For sowing sort used Maksus (Maxus) - 2400 H. Yu (ranostyhlyy, the growing season 100-110 days) of "PROHREYN" Canada grade Sasuke (Saska) - 2700 H. Yu (120-130 middle-growing season days) of "PROHREYN" Canada grade Cordoba (ranostyhlyy, the growing season 105-110 days) LLC "ZAATBAU" Ukraine. Seeding was - sort Maksus-700-750, sort of Cordoba, 500-550, 400-450-grade Sasuke. Along with planting fertilizer made Sulfamo French company Timak. After sowing had kotkuvannya ringed shporovymy rollers. After kotkuvannya on the next day spent entering soil herbicides (Stomp330 Frontyer Optima- + 2 + 0.7 l/ ha).